MINERALOGICAL ANALYSIS OF SAMPLES FROM THE BUČIM TAILING DAM DRILL HOLES (Geologica Macedonica, 2021)
The tailing dam in the Bučim mine is an important segment in the exploitation of porphyry ores from the Bučim mine and in the period of 40 years there has been deposited over 135 Mt of tailings which contains interesting contents of gold, copper, silver and other rare and dispersed elements, which at the makes the tailing dam technogenic deposit. In the framework of this paper, the mineralogical aspect of the tailings was treated on the basis of samples taken from 6 boreholes and studied 30 ore-microscopic polished sections. The detailed microscopic study confirmed the expected mineral association represented by Fe-oxides, mainly magnetite and maghemite, then chalco-pyrite, natural gold, pyrite, sulfosols and others. Scanning electron microscope study confirmed the established mineral association and gave the compositions of the major ore minerals. During the analysis and comparison with the standards for these types of mineral species, it was concluded that these are the leading minerals primarily chalcopyrite and natural gold that show a high degree of purity, where the variations of copper range from 32.43 to 34.53% Cu in chalcopyrite and from 98.73 to 98.79% Au in native gold, where small variations especially in native gold are due to the presence of Ag, Cu and Te. Similar relationships have been found in other mineral species examined under the scanning electron microscope, which can be seen from the data presented in the paper.
Keywords: Bučim copper mine; tailing; ore microscopy; mineral association; samples